Pengaruh Ukuran Perusahaan dan Likuiditas Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Varibel Intervening - Fitriani, Nabila; Khaerunnisa, Enis (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2024)
The purpose of this study is to see how the effect of company size and liquidity on firm value and the effect of profitability as a mediating variable. The research population used food and beverage subsector companies listed on the Indonesia Stock Exchange in 2012-2021 with a sample using purposive sampling method, namely 21 companies. The data was analysed with partial hypothesis testing, path analysis and sobel test. The results of the study, namely company size has no effect on firm value, liquidity and profitability have a positive and significant effect on firm value, company size has no effect on profitability, liquidity has a positive and significant effect on profitability, profitability is unable to mediate the relationship between company size and firm value, but is able to mediate the relationship between liquidity and firm value